HUBUNGAN PROGRAM MAKAN BERGIZI GRATIS (MBG) DENGAN TINGKAT KEHADIRAN SISWA KELAS V SEKOLAH DASAR - Paulus Rivaldi Pili Ngoba; Jesica Nenabu; Maria Aprilia Meli Maing; Gabriela Solsido Ametuke; Adam Bol Nifu Benu; Habibi Musa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Free Nutritious Meal Program (MBG) is a government priority policy aimed at improving children's nutritional status, promoting learning readiness, and supporting equitable distribution of educational quality. Adequate nutrition is closely related to students' cognitive development, stamina, and learning resilience, thus influencing their school attendance. This study aimed to determine the relationship between the implementation of the MBG Program and the attendance of fifth-grade elementary school students. The study used a quantitative, descriptive correlational approach, with a sample of 28 fifth-grade students, drawn using a saturated sampling technique. The instruments used were a 3-point Likert scale questionnaire and student attendance data documentation. The descriptive analysis showed an average score of 1.86 for students' perceptions of MBG, which falls into the "tend to agree" category. The median was in the "Agree" category, while the mode was in the "Disagree" category. Despite variations in perceptions, the general trend indicated a positive assessment of the MBG program. Attendance documentation data showed that students with positive perceptions of MBG had higher and more stable attendance rates. These findings indicate a positive relationship between students' perceptions of MBG and attendance, although the study did not use inferential statistical tests. Overall, the implementation of MBG is considered to have contributed to improving students' physical readiness, energy, and motivation to learn, thus increasing their school attendance.